Biodegradation of Plastics by Pseudomonas spp. Isolated from Soil Samples of Landfills in Khartoum State, Sudan - Elkhalil, Elhadi A. I.; Abbas, Yousra (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to assess the biodegradation of plastic bags by Pseudomonas spp. isolated from soil samples collected from landfills in Khartoum State, Sudan. Soil samples were collected from three different locations (A = Khartoum landfill, B = Khartoum North landfill, C = Omdurman landfill). The Identification and characterizatics of bacteria were done using morphological and biochemical characterizations. The isolated and standard strains were added to the plastic bags in liquid media and then incubated in a rotary shaker for three weeks to allow time for biodegradation. The initial and final dry weights of plastic before and after incubation in the culture medium were compared and the percentage of degradation was calculated. The data were subjected to statistical analysis using completely randomized design (CRD). Mean separations were estimated by Duncan multiple range test (DMRT). This work revealed that the landfill soil is a good source of microbes capable of degrading plastic materials. The isolated strains (Pseudomonas spp.) were found to degrade the plastic bags in the range between 76.4 to 84.8 % within three weeks. Pseudomonas putida was found to degrade the plastic bags up to 85.2 %. The weight loss in plastic bags’ samples is likely due to active enzymes produced by the bacteria